Energy Security and Sustainability in Eurasian Economic Union in the Terms of Economic Growth: The Case of Kazakhstan’s Energy Sector up to 2040 Perspectives - Movkebayeva, Galiya; Aktymbayeva, Aliya; Tyurina, Yuliya; Baikadamov, Nurken; Beketova, Kamar; Troyanskaya, Marija; Smagulova, Sholpan; Imangaliyeva, Aizhan (International Journal of Energy Economics and Policy, 2020)
The economy of Kazakhstan is the first economy in Central Asia and the second among Eurasian Economic Union (EAEU) countries after Russia. On rates of hydrocarbon raw materials extraction Kazakhstan is included into first ten countries of the world. Kazakhstani economy is based on heavy industry, ferrous and non-ferrous metals, and oil and gas. And it allows Kazakhstan is being on the road of economic growth. With economic growth, the energy production and consumption are also increasing rapidly, resulting first of all, on harmful carbon emissions. Thus, the purpose of this research is to carry out a comparative assessment in the energy sector development and to submit forecast of its demand and its environmental impact in terms of Kazakhstani economic growth up to 2040. First scenario (Base Case) assumes conventional development pattern together with neither significant changes in the patterns of energy supply and demand nor extensively changed policies and measures. The second one (Mitigation) assumes a technological improvement, regulation and industrial development policies and additional policies which have been designed to promote energy efficiency and reduce emissions across the economy. The simulations are applied until the year 2040, while 2015 is set as the base year. The findings suggest in both scenarios Kazakhstan will continue to pursue its economic development driving energy demand and carbon emissions will also raise. However, under Mitigation Scenario, emission intensity will be lower insignificantly. Keywords: Kazakhstan, energy, carbon dioxide, economic growth JEL Classifications: 0130, Q400, Q430 DOI: https://doi.org/10.32479/ijeep.9073